Mediating effect of emotionality on the intention to use the Nigerian central bank digital currency (e-Naira) - Ahmed, Mahfooz; Al-Hussaini, Abulfathi Ibrahim Saleh; Ibrahim, Adamu Abubakar; Abubakar, Raihanat Ahmad (Inderscience, 2025)
This study investigates the mediating effect of emotionality with other related technology acceptance factors influencing Nigerian retailers' decisions to adopt or reject the central bank digital currency (CBDC). Guided by the technology acceptance model (TAM), the research examines the technology adoption factors that could influence the intentions to adopt e-Naira among Nigerian retailers. A survey was conducted among retailers in Abuja, Nigeria's capital, resulting in 326 valid responses. The findings reveal that perceived ease of use, usefulness, and trustworthiness positively influence retailers' intentions to adopt e-Naira, while financial concerns have a negligible direct effect. Notably, emotionality significantly mediates the relationship between trustworthiness and financial concerns with adoption intentions, highlighting the importance of emotional factors in technology acceptance, especially when related to financial activities. These insights are valuable for policymakers, central banks, and stakeholders in promoting e-Naira adoption. By addressing the identified factors and leveraging emotional influences, stakeholders can enhance the adoption of digital currencies. This study contributes to the growing literature on CBDCs and provides actionable insights into the challenges and opportunities of integrating e-Naira into Nigeria's retail sector.